Step by step fabrication and characterization of Au (111) exposed single crystals - Darwish, Nadim; Eggers, P.; Yang, W.; Paddon-Row, M.; Gooding, J. (2010)
A detailed procedure for the fabrication of mechanically exposed Au (111) gold single crystal surfaces is reported. The procedure produced surfaces of high quality with high reproducibility. The method presented, has modifications compared to those reported previously in literature mainly with regards to the surface annealing temperatures used. The quality of the surfaces was confirmed by cyclic voltammetry in 0.1M H2SO4 and scanning tunneling microscopy (STM) which showed large triangular (111) terraces of sizes of few (100nm2) in size. The quality of self assembled monolayers (SAMs) formed by 9-mercapto-1-nonanol on such surfaces was studied by impedance spectroscopy at 0V vs Ag/AgCl. The SAM was shown to behave as an ionic insulator and is well described as a Helmholtz capacitor model. These results demonstrate that the surfaces prepared by the described procedure are ideal for studies of thiolated thin films on gold surfaces, an area of interest for electrochemical and biosensing applications. © 2010 IEEE.